REFORMATION OF THE PENSION SCHEME IN ALBANIA - Astrit Hado; Andri Koxhaj; Osman Metalla (European Scientific Journal, ESJ, 2015)
One of the main issues addressed while designing the social insurance system and the old age pension programs is how to make the system and programs produce incentives relating the savings and income redistribution as well as to function on the insurance principle (1). The saving consists in smoothing consumption over life time, postponement of consumption from early life time, period of active work and higher earnings to the old age period, when incomes are lower and due to old age it is impossible to generate earnings. Redistribution consists in transferring life time incomes from a person to another in retairement age in order to avoid poverty. A person with low incomes during the life time could save sufficiently for the old age period but this probably could lead to poverty during the working period. The redistribution avoids this fenomenon and create a beter financial situation for all in old age period. Functioning upon the insurance principle entails payment of social insurance contributions during the economic activity period in order to be entitled to a future pension in respect of old age when no earnings can be generated.